Hypertensive Disorders of Pregnancy and Preterm Birth Rates among Black Women - Premkumar, Ashish; Baer, Rebecca J.; Jelliffe-Pawlowski, Laura L.; Norton, Mary E. (American Journal of Perinatology, 2019)
Objective The objective of this study was to investigate the role of gestational hypertension (gHTN) and chronic hypertension (cHTN) on rates of preterm birth (PTB) among black women.Study Design Singleton live births between 20 and 44 weeks' gestation among black women in California from 2007 to 2012 were used for analysis. Risk of PTB by subtype and gestational age among women with cHTN or gHTN, including preeclampsia, was calculated via Poisson's logistic regression modeling. Risks were adjusted for maternal factors associated with increased risk of PTB.Results A total of 154,950 women met the inclusion criteria. Of the 5,948 women in the sample with cHTN, 26.2% delivered preterm; for the 11,728 women with gHTN, 21.6% delivered preterm. Women with gHTN or cHTN had a higher risk of medically indicated and spontaneous PTB, both at less than 32 and 32 to 36 weeks, when compared with nonhypertensive women (adjusted relative risks [aRRs]: 3.4–11.6). Women with superimposed preeclampsia had higher risks of spontaneous (aRR: 2.8, 95% confidence interval [CI]: 2.3–3.4) and medically indicated PTB (aRR: 2.8, 95% CI: 2.0–3.8), especially PTB < 32 weeks, when compared with women with preeclampsia.Conclusion Among black women, superimposed preeclampsia increased the risk for spontaneous and medically indicated PTB, especially PTB < 32 weeks.
Keywords: hypertension; preterm birth; health; racial/ethnic disparities